Parallel and distributed computing on multidomain non-routable networks. (1st January 2011) - Frattolillo, Franco; Landolfi, Federica
Middlewares are software infrastructures used to cluster heterogeneous and geographically distributed computational resources so as to exploit them as computing systems able to run large-scale applications. Although their main aim is to transform the internet into a sort of computational grid to which everyone can connect in order to execute distributed applications, a number of problems have still to be solved in order to make middlewares actually effective in such a context. For instance, exploiting computational resources available within 'departmental' organisations can be still considered a difficult task, since such resources are usually represented by computing nodes which belong to non-routable, private networks and are connected to the internet through publicly addressable IP front-end nodes. This paper presents a Java middleware that can support the execution of large-scale applications over heterogeneous multidomain, non-routable networks. In fact, the middleware can be also exploited to relieve programmers of the classic burden tied to the deployment of PVM run-time libraries and program executables among computational resources belonging to distinct network administrative domains.